0.4(3x-1)=0.5(x+1)

Simple and best practice solution for 0.4(3x-1)=0.5(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.4(3x-1)=0.5(x+1) equation:



0.4(3x-1)=0.5(x+1)
We move all terms to the left:
0.4(3x-1)-(0.5(x+1))=0
We multiply parentheses
1.2x-(0.5(x+1))-0.4=0
We calculate terms in parentheses: -(0.5(x+1)), so:
0.5(x+1)
We multiply parentheses
0.5x+0.5
Back to the equation:
-(0.5x+0.5)
We get rid of parentheses
1.2x-0.5x-0.5-0.4=0
We add all the numbers together, and all the variables
0.7x-0.9=0
We move all terms containing x to the left, all other terms to the right
0.7x=0.9
x=0.9/0.7
x=1+0.2/0.7

See similar equations:

| a^2=3a+8 | | 60+2x=120–x | | 60+2x=120–x, | | 3x–57=88 | | 15p^2+5p=20 | | 15^2p+5p=20 | | 2/3x-5=4+x | | (x+9)/5=-9 | | 18-4y=10 | | (7)(17.5)=3x | | -3(3p+6)-2(2-14p)=3(4+6p) | | -5(-2x+8)-8(-5-5x)=48+51x | | 8x+5x+3+7=10x+4+2x | | 6x+5+5x-2=5x+6x-11 | | 5b²+4=-12b | | 4/6w=-4 | | 10x10^2x=6 | | 5(4r)=-80 | | 5a²+15a=0 | | -3x+11-5=11 | | 7x-1/4-1/3(2x-1-x/2)=10/3 | | 3(x-8)=5x+9 | | (3x)/10=-9 | | 4m^2-20m+53=D | | (x+10)/7=-2 | | -5/3=1/2x-3/4 | | 0=4x^2-49x | | 0.7w-0.4+0.2w=4 | | 350=5+x285 | | 8x+4x-4x=40 | | X-21=711-c | | 3(x-1)=(2x+3) |

Equations solver categories